Readiness of Health Cadres as Promoters of Adaptation to New Habits of Covid-19 - Betie Febriana; Dwi Happy Rochmawati (GLOBAL HEALTH SCIENCE GROUP, 2021)
The application of the new normal policy order is an adaptive response to the existence of the current pandemic. Mental health and psychosocial support training is an alternative to support this. The purpose of this study was to determine the effectiveness of training on the readiness of mental health cadres to adapt to new habits. Readiness is assessed from knowledge and stress. This is pre-experimental design research used a single group pretest-posttest. The research sample was 60 people who could read and write, committed to participating in the training for three consecutive days. the sample was taken using purposive sampling technique. Data was obtained using a questionnaire and analized by the paired t test. The results showed that there was an average difference between pre-test and post-test, meaning that the intervention had an effect on increasing knowledge and decreasing respondents' stress.